2014
DOI: 10.1074/jbc.m113.537167
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Strategies for Catalysis Adopted by Evolutionary Distinct Family 43 Arabinanases

Abstract: Background: Arabinanases are key enzymes involved in hemicellulose degradation. Results: Crystallographic, mutational, and biochemical assays of three arabinanases reveal the molecular mechanisms governing their catalysis and activation. Conclusion: Accessory domain and metal ion are essential for catalysis. Structural adaptations in the catalytic interface confer unique action modes to ruminal arabinanases. Significance: This work provides new molecular strategies for arabinan hydrolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 60 publications
3
31
0
1
Order By: Relevance
“…This study demonstrates the potential of combining rational design with evolutionary diversity to unravel new activities and modes of action and, in particular, the importance of the β‐propeller hollow properties for GH43 catalytic function as proposed in our previous work (Santos, Polo et al, ). In addition, these results expand our current mechanistic understanding about this fundamental GH family for most cellulolytic microorganisms.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…This study demonstrates the potential of combining rational design with evolutionary diversity to unravel new activities and modes of action and, in particular, the importance of the β‐propeller hollow properties for GH43 catalytic function as proposed in our previous work (Santos, Polo et al, ). In addition, these results expand our current mechanistic understanding about this fundamental GH family for most cellulolytic microorganisms.…”
Section: Introductionsupporting
confidence: 67%
“…Detailed structural analysis of the wt BlXynB revealed that the side chain of the catalytically relevant histidine (His 245 ) adopts an unusual rotameric conformation disrupting the hydrogen bond network supporting the catalytic residues. The His 245 side chain is supposed to adopt a perpendicular configuration in relation to the acidic catalytic residues, avoiding specific hydrogen bonds with these residues that could perturb the active‐site geometry (Santos, Polo et al, ). However, in the wt BlXynB structure, the adopted rotameric conformation of His 245 led to a direct interaction with the pKa modulator Asp 136 , which is critical for maintaining the general acid residue in a proper and productive orientation (Brüx et al, ; Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…The identity of the metal ion in W Araf43, however remains ambiguous, with Ca 2+ or Mg 2+ as most likely candidates. Other studies have shown that enzymes in GH43, such as ARN2 and ARN3 from a rumen metagenome (classified under subfamilies 4 and 5, respectively), present a calcium‐independent mechanism . In these enzymes, a sodium or magnesium ion may be a substituent for the calcium ion, and may have a related function.…”
Section: Resultsmentioning
confidence: 99%
“…; Santos et al . ). In contrast, Cu 2+ , Ni 2+ , Co 2+ and NH 4+ strongly inhibited the β ‐xylosidase activity of XylM1989.…”
Section: Discussionmentioning
confidence: 97%
“…Regarding the biochemical characterization, the three bivalent cations Ca 2+ , Mg 2+ and Mn 2+ clearly enhanced the activity of XylM1989, thus indicating that such cations are important as enzyme cofactors. A role in the enzymatic reaction, for example, by binding and stabilizing the substrate at the active site, may be invoked (Mora€ ıs et al 2012;Ahmed et al 2013;Santos et al 2014). In contrast, Cu 2+ , Ni 2+ , Co 2+ and NH 4+ strongly inhibited the b-xylosidase activity of XylM1989.…”
mentioning
confidence: 99%